2016
DOI: 10.1002/smi.2687
|View full text |Cite
|
Sign up to set email alerts
|

Savouring and Self‐compassion as Protective Factors for Depression

Abstract: Within positive psychology, researchers and clinicians vocalize the need to expand upon how the treatment for major depressive disorder is conceptualized and implemented. The impetus of the current study was to examine preliminary criteria for identifying savouring and self-compassion as protective factors for depression. Undergraduate students (N = 133) completed a series of surveys at two points in time, 5 weeks apart. Results revealed that savouring and self-compassion were inversely related to depression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 50 publications
6
35
0
2
Order By: Relevance
“…positive/negative) that individuals encountered. One recent study reported that the association between negative life events and depression became weaker at higher levels of perceived capability of savoring (Ford, Klibert, Tarantino, & Lamis, 2017). Our results extend the current evidence by investigating the role of perceived capability of savoring and trait positive rumination in the associations between both positive and negative events and everyday emotions.…”
Section: Moderation Effects Of Savoring and Positive Rumination On Evsupporting
confidence: 85%
“…positive/negative) that individuals encountered. One recent study reported that the association between negative life events and depression became weaker at higher levels of perceived capability of savoring (Ford, Klibert, Tarantino, & Lamis, 2017). Our results extend the current evidence by investigating the role of perceived capability of savoring and trait positive rumination in the associations between both positive and negative events and everyday emotions.…”
Section: Moderation Effects Of Savoring and Positive Rumination On Evsupporting
confidence: 85%
“…As such, it is important to examine the relationship between savouring and negative (e.g., less depression and anxiety) and positive (e.g., greater life satisfaction) indicators of better adjustment. In a study on stressful life events experienced by college students, savouring at Time 1 predicted less depression at Time 2 (even after Time 1 depression was controlled for; Ford et al, ). Analyses controlling for a history of depression found that savouring related to less anxiety symptoms (Eisner, Johnson, & Carver, ), indicating that, in the study of savouring, it is important to study both depression and anxiety as separate indicators of distress.…”
Section: Savouring In Relation To Stress and Coping Theorymentioning
confidence: 99%
“…More recently, there has been increasing research on the important role savouring might play in the adjustment to a stressful life event. For example, the relationship between savouring capacity and better psychological adjustment is found in the context of stressful life events, such as negative life events in college life (Ford, Klibert, Tarantino, & Lamis, ), combat exposure (Sytine, Britt, Pury, & Rosopa, ), and stressful events in the couple life (Samios & Khatri, ). Further, neuroscience research supports the restorative function of reminiscing or recalling positive memories in the context of stress (Speer & Delgado, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because depression tends to have high autocorrelation by using short time intervals, about 1 month, between‐survey administrations comparatively generated very high covariance between depression scores at T1 and T2. In this case, high covariance left little residual variance for predictors to account for T2 depression scores, given previous research (e.g., Ford, Klibert, Tarantino, & Lamis, ; Haeffel & Vargas, ). Examining the effects predicting T2 depression with the addition of new variables after controlling for the effect of T1 depression, a R 2 change value increment of .04 for T2 depression showed a meaningful contribution to the existing variables (Ford et al ., ).…”
Section: Discussionmentioning
confidence: 75%
“…In this case, high covariance left little residual variance for predictors to account for T2 depression scores, given previous research (e.g., Ford, Klibert, Tarantino, & Lamis, 2016;Haeffel & Vargas, 2011). Examining the effects predicting T2 depression with the addition of new variables after controlling for the effect of T1 depression, a R 2 change value increment of .04 for T2 depression showed a meaningful contribution to the existing variables (Ford et al, 2016). It is recommended that future research prospectively evaluates the direct effects of positive emotion in distress on depression by using longer time intervals between survey administrations.…”
Section: Discussionmentioning
confidence: 85%